Microcredit and the Socio-cultural Obstacles to Women’s Empowerment in Northern Territories of Ghana - Jenkıns, Hatice; Batınge, Bibiana Koglınuu (My University, 2018)
This study investigates the impact of microfinance programmes onwomen’s empowerment in the northern territory of Ghana, which isknown as the poorest part of the country. A survey methodology is used tocollect data from a sample of 247 female entrepreneurs and theirhusbands (189 women and 58 men) in rural areas. The majority of thesample are aged 40 or below, and many are illiterate. The researchfindings indicate that although microfinance appears to have somepositive effects on women’s income, it is insufficient to ease thehardships in the lives of women in northern Ghana. Most femalerespondents indicated that women are largely forbidden by men to ownproductive assets such as land and livestock. The traditional domineeringbehaviour of men remains a significant obstacle. Despite the increase inaccess to credit, microfinance itself may not be sufficient to eliminatebarriers to women’s empowerment and to the reduction of poverty.
Keywords: Ziraat Mühendisliği; Kadın Araştırmaları; İktisat